(untitled) (Semiárida, 2020)
The objective of was to determine the influence of grazing methods with a relatively low or high herbage allowance in the first 84 gestation days on ewes/lambs daily weight gain (DWG) and area production. The study was conducted at an 8.4 ha natural grassland in South Brazil. During the winter, early pregnancy ewes were submitted to two grazing methods (continuous (CS) and rotative (RS) stoking) and two herbage allowances (HA; 12 and 18% live weight)), resulting in four treatments: CS18, CS12, RS18 and RS12. It was measured the DWG and body condition score (BCS) from ewes and from ewes and lambs after born, as well lambs area production. During the winter only the HA change the DWG from the ewes. During the spring differences were found only in the lambs DWG from grazing method, been higher in CS. A grazing method × HA interaction indicate that the higher lambs area production was achieved in the CS12 treatment. The results indicate that the grazing methods and HA had a little influence in the animal performance over winter and the herbage could be better used in this period.